Judicial enforcement of the Constitution and judicialization of social rights - Bertelsen Repetto, Raúl (Derecho Público Iberoamericano, 2019)
This paper critically examines one of the key factors to judicial activism, namely, the legal character of the Constitution. Throughout a comparative analysis, the author puts under question the premise that all constitutional provisions are judicially enforceable by its own nature. Specifically, this work looks carefully into the legal status of social rights and argues from different perspectives that Congress and not the Judiciary has the primacy on the configuration of such positive rights. Consequently, judges are bounded by statutory law when it comes to decide what the scope of social right is.